Contribuições do pensamento computacional no aprendizado da resolução de situações-problema no campo aditivo - Romero, Julio Cezar (2020)
Computational Thinking - PC is characterized by being a set of cognitive processes of computer science for the resolution of problems, being applied in distinct areas of knowledge. The Common National Curriculum Base – BNCC mentions the term PC associating Mathematics as a strategy to "translate" problem situations. Therefore, how can PC contribute to the learning of problem-solving in the additive field in a 4th grade class? The choice of this research topic is justified because it is believed that PC can help in the construction of mathematical reasoning aiming at satisfactory results in the development of skills and competences needed by students during the whole school period and that it will certainly also be used in any profession they choose. The objective of the research is to investigate if students of Basic Education, using Jean Piaget's Construtivism processes followed by Seymour Papert's Construcionism, are motivated to participate in playful activities according to their respective ages and that stimulate the development of PC and its concepts. The methodology used was Bardin's Data Analysis (2010), which presented qualitative and quantitative data. The results after the application of the research found that the use of PC concepts are beneficial for the child in terms of understanding mathematical problem-solving, in the additive field, when comparing pre and post-test activities, as well as the motivation in performing activities based on PC concepts, as pointed out by the Constructivist and Constructivist theories.